Volatility-of-volatility risk - Darien Huang; Christian Schlag; Ivan Shaliastovich; Julian Thimme (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
We show that time-varying volatility of volatility is a significant risk factor which affects the cross-section and the time-series of index and VIX option returns, beyond volatility risk itself. Volatility and volatility-of-volatility measures, identified modelfree from the option price data as the VIX and VVIX indices, respectively, are only weakly related to each other. Delta-hedged index and VIX option returns are negative on average, and are more negative for strategies which are more exposed to volatility and volatility-of-volatility risks. Volatility and volatility of volatility significantly and negatively predict future delta-hedged option payoffs. The evidence is consistent with a no-arbitrage model featuring time-varying market volatility and volatility-of-volatility factors, both of which have negative market price of risk.
urn:nbn:de:hebis:30:3-466768
Keywords: G12; G13; 330; volatility of volatility; hedging errors; risk premiums